An Efficient Cluster based Co-Operative-ED Max Selection Algorithm for Improving the Detection Accuracy of SU Nodes in CR - WSN - Vignesh, G D; Sabaridharan, V P; Balamurugan, A M; Ronald, T Rex (2024 First International Conference on Software, Systems and Information Technology (SSITCON), 2024)
Cognitive Radio-Wireless Sensor Networks (CR-WSNs) offer a solution to the spectrum limitations faced by traditional Wireless Sensor Networks (WSNs) by utilizing idle frequencies within licensed bands. By detecting and exploiting these spectrum holes, CR-WSNs can reduce interference and enhance network performance. However, energy conservation is a critical concern due to the limited battery capacity of sensor nodes. This research paper proposes a collaborative based sensing methodology using the Energy Detection (ED) technique, analyzed under different decision-making logics: AND, OR and the proposed Max Selection scheme. The Max Select scheme aims to significantly improve the detection accuracy while minimizing the probability of false alarms, compared to the conventional ED technique. By efficiently managing the energy resources and enhancing the sensing performance, the proposed scheme addresses key challenges in CR-WSNs, balancing the need for reliable spectrum detection with the constraints of energy consumption in these networks.